JAPAN FOREIGN POLICY IN COUNTERING THE ISIS TERRORISM - Ahmad Soim (HI 16 UMY 063, 2016)
*63 The Islamic State of Iraq and Syria (ISIS) currently become the central of attention of the global community. As a terrorist group, ISIS had done several brutal actions which threaten the global security. As the result, several areas in Iraq and Syria had occupied by ISIS as their base. The threat which ISIS gave was not only in Iraq and Syria. Some international communities had felt the ISISâ€™s brutality including Japan losing the two of its Japanese journalists which were beheaded by this terrorist group. As the result, Japan responded this incident by releasing â€œthree-pillar foreign policyâ€ as the response in countering the ISIS terrorism. However, when the other states responded the ISIS by military forces by implementing the foreign policy, Japan just participated in countering the ISIS by doing soft way. This research aims at examining the considerations of Japan in deciding its foreign policy in countering the ISIS terrorism. As it is foreign policy had released, Japan responded the ISIS by doing soft way as it is mentioned in its â€œthree-pillars foreign policyâ€. However, the other states which involved in the battlefield in fighting against ISIS used their military forces. Therefore, it is interesting to analyze Japanâ€™s considerations by doing so, while the other states directly attacked ISIS by military means. The method of writing in this thesis is using qualitative method. Therefore, in this writing, the writer uses several ways to collect the data in order to discuss the problem. The first is media research, the second is library research, the third is data analysis, and the last is proving hypothesis. By completing the process of this research, the writer found that the consideration of Japanese domestic politics and the international situation at the mean time becomes the reasons why Japan took the policy in countering the ISIS terrorism by that way. Keywords: Japan, Foreign Policy, ISIS, Terrorism